Banking integration in the euro area - Inês Cabral; Frank Dierick; Jukka Vesala (European Central Bank (ECB), 2002)
This paper provides an assessment of the degree of integration in banking services in the euro area. It diverges from the typical analysis on integration in the financial sector by focusing on the main financial products and services provided by banks to corporate and personal clients rather than on financial markets. As the “law-of-one-price” concept is often not applicable to banking products and services, a wide range of quantitative and qualitative indicators of integration is used in the analysis. Indicators of integration are reviewed for three product areas: wholesale (unsecured interbank loans and deposits, repo market) capital market-related (corporate finance services, asset management and trading) and retail (directed to households and small firms). The main conclusions are that while the market on wholesale banking services is strongly integrated and integration is advancing at a fast pace in capital market-related activities, market segmentation is still significant at the retail level.
Keywords: 330; Finanzsektor; Bank; EU-Binnenmarkt; Marktintegration; EU-Staaten